Five Year Plan (1990-95) Central Sector Schemes Relating To Irrigation, Flood Control and Farakka Barrage Project (Vol.III) - Planning Commission (Planning Commission, 1990)
The Centrally Sponsored CAD programme initiated in 1974-75 with the basic objectives of improving the utilisation of created Irrigation potential of selected major/medium irrigation commands and consequently on its productivity presently covers around 131 projects in 20 states and 2 Union Territories covering a Culturable Command Area (CCA) 18.5 M.ha.
Government of India Ministry of Water Resources
Government of India Ministry of Water Resources